2017
DOI: 10.1016/j.ajme.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Current status of multi-detector row helical CT in imaging of adult acquired pancreatic diseases and assessing surgical neoplastic resectability

Abstract: Background: It is usually hard to detect pancreatic lesions early as the pancreas lays retro peritoneum so it cannot be assessed during a routine physical exam. By the time a person has symptoms, the disease has already established morphological imaging CT changes. Objective: The objective of our study was to clarify the role of multidetector computerized tomography (MDCT) in different adult acquired pancreatic diseases and assess the efficacy of surgical pancreatic tumors resectability preoperative. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…And, Compared to our study, 15 patients showed hypodense lesions, (61.2%) of tumors occupied the head of the pancreas, that may explains why (77%) of patients had a clinical history of jaundice because (61%) of the masses occupied pancreatic head. (23) In the study of Vargas et al (2004), 25 patients involved in the study, 20 tumors masses (80%) were hypodense, one (4%) was mixed density, and 4 (16%) were considered isodense in comparing to normal pancreatic parenchyma, in our study 15 lesions(83.3%) were hypodense, 1 (5.5%) was mixed and 2 (11.1%) were isodense. (24) In our study (more than one criterion was detected in same patient) Liver metastasis was detected by MDCT in 8 patients (44.5%).…”
Section: Acute Pancreatitissupporting
confidence: 46%
See 1 more Smart Citation
“…And, Compared to our study, 15 patients showed hypodense lesions, (61.2%) of tumors occupied the head of the pancreas, that may explains why (77%) of patients had a clinical history of jaundice because (61%) of the masses occupied pancreatic head. (23) In the study of Vargas et al (2004), 25 patients involved in the study, 20 tumors masses (80%) were hypodense, one (4%) was mixed density, and 4 (16%) were considered isodense in comparing to normal pancreatic parenchyma, in our study 15 lesions(83.3%) were hypodense, 1 (5.5%) was mixed and 2 (11.1%) were isodense. (24) In our study (more than one criterion was detected in same patient) Liver metastasis was detected by MDCT in 8 patients (44.5%).…”
Section: Acute Pancreatitissupporting
confidence: 46%
“…Tadros and, Remon Zaher Elia (2016) showed Liver metastases were detected by 7 patients (50%),ascites in 2 patients (14%) and Osteolytic bony lesions were found in (7%). (23) Assessment of vascular invasion is an important parameter for determining resectability of pancreatic cancer (26) In their study, Vyacheslav I Egorov et al found vascular involvement of patients with pancreatic carcinoma ranges between (21%-64%), most often with involvement of SMA, due to its location (27) . In our study, 8 patients (44.4%) showed a vascular involvements, among them SMA and splenic artery were the most involved arteries, while SMV and splenic vein were the most involved veins.…”
Section: Acute Pancreatitismentioning
confidence: 99%
“…The combined use of multiplaner reformatting (MPR) and minimum intensity projection (MinIP) techniques significantly improves the visualization of the biliary ducts and their site of confluence compared with those obtained by axial CT. Moreover, MinIP technique enables us to depict the small biliary duct and the pancreatic duct more clearly [15][16][17].…”
Section: Introductionmentioning
confidence: 99%